Pendekatan Semivariogram Anisotropik dalam Metode Ordinary Kriging (OK) terhadap Pola Penyebaran Mineral Ikutan Timah - Ririn Amelia; Guskarnali Guskarnali (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2020)
Unconventional mining is still the choice of the people of Bangka Island. One of the locations on the Bangka islands that still conduct tin mining activities on a small scale or community scale is Sambung Giri Hill, Merawang District, Bangka Regency. Based on understanding distribution patterns of the mineral will provide a general description that can prevent and minimize damage caused by mining activities. Interpolation of Tin (Sn), zircon (Zn) and hematite (Fe2O3) using anisotropic semivariogram in the Ordinary Kriging method uses the distribution pattern of each of these minerals. In this method uses the best anisotropic semivariogram model of each mineral. Models that are more suitable for hematite and zircon minerals are exponential, whereas tin uses the Gaussian model. Based on the results of the Ordinary Kriging method, the mineral distribution pattern was obtained in accordance with the east direction around the Sambung Giri Hill. The estimated pattern of mineral distribution, provides a general description that can minimize environmental damage due to mining activities in Sambung Giri Hill.